I Just Can’t Control Myself: A Self-Regulation Perspective on the Abuse of Deviant Employees - Mawritz, Mary B.; Greenbaum, Rebecca L.; Butts, Marcus M.; Graham, Katrina A. (Academy of Management Journal, 2017)
Drawing on self-regulation theory, we contribute to the abusive supervision literature by testing supervisors’ self-regulation impairment as a key mediator of the relationship between subordinate deviance and abusive supervision. Further, given that the process underlying the relationship between subordinate deviance and abusive supervision may be explained by social exchange theory, we examine the differential strength of supervisor self-regulation impairment versus social exchange as mediating mechanisms. We also explore the moderating effects of subordinate performance and supervisor bottom-line mentality (i.e., a one-dimensional frame of mind that revolves around securing bottom-line outcomes to the neglect of competing priorities) on the relationship between subordinate deviance and supervisor self-regulation impairment. We found that supervisor self-regulation impairment mediated the relationship between subordinate deviance and abusive supervision, and the indirect effect was stronger in the presence of high subordinate performance and high supervisor bottom-line mentality. We then replicated these findings in a longitudinal field study across four time periods, and demonstrated that self-regulation impairment provides a stronger explanation for the relationship between subordinate deviance and abusive supervision than social exchange. The theoretical and practical implications of our research are discussed.